Carbon prices, climate change mitigation & food security: How to avoid trade-offs? - Frank, Stefan; Havlík, Petr; Valin, Hugo; Wollenberg, Eva Karoline; Hasegawa, Tomoko; Obersteiner, Michael (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
Carbon price policies deliver cost-efficient mitigation across sectors, but can result in tradeoffs with food security and other sustainable development goals. Scenarios for a 1.5 °C world based on carbon prices could increase the undernourished population by 80 - 300 million in 2050. Applying a uniform carbon price across geographic regions and economic sectors has inequitable effects on countries’ agricultural competitiveness and food availability. Under higher carbon prices, regions with poor productivity – and consequently higher GHG emissions per unit of output – would experience increased agricultural commodity prices.